Child Discipline in Times of Conflict. (July 2020) - Malcolm, Michael; Diwakar, Vidya; Naufal, George
Using a unique pairing of household survey data and geolocational conflict data, we investigate the relationship between conflict intensity and the disciplinary methods employed by Iraqi households. We find that parents in high-conflict areas are more likely to use moderate and severe corporal punishment and are less likely to use constructive parenting techniques like redirection. A corresponding difference-in-differences analysis confirms the nature of this association. While there is a general sense that war has profound long-term impacts on the psychological health of children, research on transmission mechanisms remains limited. Given the persistence of early childhood outcomes into adulthood, these results are potentially an important piece of assessing and mitigating the long-term costs of war on civilian populations.